The Influence of a Collagen-Based Multiple Ingredient Supplement on Muscle Performance - Hatchett, Andrew; Gregory, Rhiannon; Shick, Annelise; Armstrong, Kaitlyn (Journal of Sports Research, 2022)
Nutritional supplementation is a common practice athletes engage in to enhance performance. Innovation in nutritional supplements are common but rarely tested in a clinical setting. The purpose of this research was to determine the influence of a novel enzyme hydrolyzed collagen based multiple ingredient supplement has on muscular performance. Eight healthy recreationally trained participates completed three data collection sessions (baseline, 10-days and 21-days). Each session consisted of the following assessments: body composition upper and lower body power, upper and lower body strength, upper body endurance and midline endurance. Measures from each session were compared to determine if a significant change in performance was observed. After comparing the first data collection session to the last collection session there were statistically significant changes in several performance measures. Lower body power (p=0.007), upper body power (p=0.015), lower body strength (p=0.004), upper body endurance (p=0.043). Additional significant differences in muscle performance were observed between the first and second assessments as well as between the second and third assessments. Based upon the results of this research the use of an enzyme hydrolyzed collagen based multiple ingredient supplement can positively influence muscular performance.